IMPROVEMENT OF MAQOSHID SHARIAH PERFORMANCE - Delli Maria; Fitri Agustina (Saburai International Journal of Social Sciences and Development, 2018)
The purpose of this study is to examine, whether the Shariah Supervisory Board can improve the performance of Maqosid Shariah on Islamic banking in Indonesia. This study hypothesises that Islamic Banking with implemetation Shariah Supervisory Board and Independent Board of Commissioners have higher performance of maqosid shariah. Performance of maqosid shariah is measured using maqasid syariah with simple addictive weighting method. The study uses 12 Syaria Bank in Indonesia. The paper finds that the multiple position of Shariah Supervisory Board and Independent Board of Commissioners has contributed to the maximum improvement of Shariah Bank Performance, and will to the existing literature on Islamic Bank, business ethics, firms governance. It provides evidence on Syariah Bank in Indonesia